Owning our off-ramps - Paul N. Foster (Greater Baltimore Medical Center, 2015)
In this issue of JCHIMP, Meade et al., publish the results of qualitative analysis regarding a second-year rotation in tracing the outcome of discharged patients. They report that their residents develop remarkable insights into the types of failures and miscommunications that plague our discharge processes. This perspective piece places this article in the context of literature seeking to understand why these problems are endemic and how we must prioritize efforts to address and prevent them.